The effect of skimming and scanning techniques on coastal students’ reading comprehension - Saputra, Rama Rendra; Subroto, Gatot; Nopita, Dewi (Lembaga Penelitian, Penerbitan, Pengabdian dan Pengembangan Masyarakat (LP4M) Unmuha, 2025)
Junior high school students still experience significant difficulties in reading comprehension, particularly when dealing with narrative texts that require the ability to distinguish between main ideas and supporting details. This study aimed to investigate the effect of skimming and scanning strategies on the reading comprehension of eighth-grade students at SMPN 14 Tanjungpinang, Riau Islands, Indonesia. Employing a quantitative approach, the study used a pre-experimental one-group pre-test and post-test design involving 24 students. The research instrument was a reading comprehension test consisting of ten essay questions, which was administered before and after the treatment across four instructional sessions. The results revealed a significant improvement in students’ reading comprehension following the implementation of skimming and scanning strategies. These strategies effectively assisted students in identifying main ideas and specific information in narrative texts, leading to improved overall comprehension. Therefore, skimming and scanning can be considered effective techniques for enhancing students’ reading comprehension and English literacy.